User command acquisition based IoT automatic control system - Inshik Kang; Hyunok Song; Hoekyung Jung (Institute of Advanced Engineering and Science, 2019)
Recently, researches are being conducted to build a smart environment using various sensors and devices and to provide customized services to users through IoT (Internet of Things). The existing IoT system operates the device only by using the threshold value. So, there are problems that device operates when a service that does not consider a user characteristic is provided or when user not necessary. In this paper, to solve these problems, the system collects the remote control commands and compares it with the value of device operation threshold and sets the changed threshold value. In addition, devices not registered in the server constitute the environment by linking with existing task. Therefore, it is possible to provide a customized service to the users.